Pengaruh Penghindaran Pajak Dan Risiko Pajak Terhadap Biaya Utang Studi Kasus Pada Perusahaan Sektor Makanan Dan Minuman - Rifdah Riyan Dara; Tiari Dakhi; Sovia Lolita Apriani Pardede; Corrina Wongsosudono; Mutia Riska Faridani; Hasrul Siregar (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2024)
This research aims to determine the effect of debt costs. The variables tested in this research are tax avoidance and tax risk as independent variables. The dependent variable used is the cost of debt. The population studied in this research were 72 food and beverage sector companies listed on the Indonesia Stock Exchange in 2018-2021. The sample in this research was 11 companies selected based on the purposive sampling method. The data analysis technique used was multiple linear regression analysis using the SPSS version 26.0 application. The results of this research show that partially the influence of tax avoidance and tax risk has no effect. The conclusion is that partially the influence of tax avoidance and tax risk has no effect. Meanwhile, simultaneously the influence of tax avoidance and tax risk has no effect on the cost of debt.